Implementation of the supervisory function in fostering the competence of the principal's academic supervision on the performance assessment of kindergarten teachers - Rosmala Dewi; Niswanto Niswanto; Khairuddin Khairuddin (STAI Hubbulwathan Duri, 2022)
The purpose of this study is to describe how the implementation of the supervisory function in fostering the competence of the principal's academic supervision on the performance assessment of kindergarten teachers in Banda Aceh City. This study uses a descriptive qualitative approach. The research was conducted at the Kindergarten in Banda Aceh City. Data collection techniques using observation, interviews. The standard of data validity in qualitative research refers to the standards of credibility, transferability, dependability, and confirmability. The data analysis technique used is descriptive qualitative analysis with data reduction techniques, data presentation, and drawing conclusions. The results of this study are the results of this study conclude that the supervision carried out by the principal on the implementation of the Teacher Performance Assessment has been carried out systematically and programmed, so that teachers feel the assistance of the principal in improving their performance. Factors that support the successful implementation of the supervisory function in fostering the competence of principals' academic supervision on the implementation of teacher performance are the factors of principals and teachers who have a desire to improve their performance through academic supervision activities shown by a cooperative attitude towards the supervision process. Meanwhile, the obstacles are the principal's lack of knowledge about Teacher Performance Assessment, the number of teachers who must be fostered and the lack of intensity of academic supervision of teachers. Meanwhile, the solution is to follow teacher performance appraisal training, increase the intensity of class visit supervision and increase academic supervision development programs and teacher performance appraisals on a regular and continuous basis.